2020
DOI: 10.3390/coatings10100996
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Treatment Induced Fluoride Conversion Coating without Pores for High Corrosion Resistance of Mg Alloy

Abstract: Fluoride conversion (MgF2) coating with facile preparation and good adhesion is promising to protect Mg alloy, but defects of pores in the coating lead to limited corrosion resistance. In this study, a compact and dense MgF2 coating was prepared by the combination of fluoride treatment and ultrasonic treatment. The ultrasonically treated MgF2 coating showed a compact and dense structure without pores at the frequency of 28 kHz. The chemical compositions of the coating were mainly composed of F and Mg elements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Another bioactive chemical conversion coating is fluoride conversion coating which forms an insoluble Mg fluoride (MgF 2 ) layer. Ultrasonic fluoride treatment and double layer Mg/fluoride-Mg/phosphate treatments increased Mg alloys’ corrosion resistance, biocompatibility and bioactivity [ 155 , 156 ].…”
Section: Bioactive Coatingsmentioning
confidence: 99%
“…Another bioactive chemical conversion coating is fluoride conversion coating which forms an insoluble Mg fluoride (MgF 2 ) layer. Ultrasonic fluoride treatment and double layer Mg/fluoride-Mg/phosphate treatments increased Mg alloys’ corrosion resistance, biocompatibility and bioactivity [ 155 , 156 ].…”
Section: Bioactive Coatingsmentioning
confidence: 99%
“…As a result, the future focus may be on enhancing the barrier effect and binding force for a full-life corrosion-resistant service. In this regard, composite coating may be a viable option for increasing the adhesion force of organic biopolymer coating [117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Furthermore, the formation of composite coatings not only improves corrosion resistance but also endows the Mg alloys with potential bioactivity and biocompatibility in long-term tests.…”
Section: Discussionmentioning
confidence: 99%
“…Under chronic exposure, significant loss of dendrite and soma of neurons induced down-expressions and other behavioural deficits [ 6 , 100 ]. Fluoride Conversion Coatings (FCCs): Several authors [ [101] , [102] , [103] , [104] ] reported the development of FCCs on Mg alloys for biomedical implant applications. The coating procedure is typically performed by immersing Mg or Mg alloy substrates in 40%–48% hydrofluoric (HF) acid solution [ 69 , 105 ].…”
Section: Coatings and Their Current Statusmentioning
confidence: 99%